Hamstring Shortness among Undergraduate Students, Using Knee Extension Angle Test - Ishaque, Farhan; Bano, Saira; Khan, Hamna; Kumar, Suneel; Qaiser, Saeed; Khan, Muhammad Asif (Journal of Rawalpindi Medical College, 2022)
Objective: To examine the causes and incidence of hamstring tightness/shortness among undergraduate physical therapy students. Cross-sectional study. Institute of Physical Medicine & Rehabilitation, DUHS during the period of Jan 2019 to Jun, 2019. Material and Methods: The subjects sample size (n=248) was estimated by open EPI software. Male and female both are included. Hamstring muscle shortness was assessed by a gold standard assessment tool i.e. passive knee extension angle test. Descriptive statistical analysis was done by using SPSS version 24. Results: The hamstring muscle tightness was measured by using knee extension angle test. It results conclude that among (248) students (62.90%) had hamstring muscle tightness / shortness and (37.10%) did not show any muscle shortness. Out of (216) females participants (136) have hamstring shortness. On the other hand out of (32) male participants (20) had hamstring shortness/tightness out of total (248) students. It was also evident from the study that 27% of physiotherapy students having low back pain was because of clinical exposure and tight hamstrings muscles. Conclusion: Hamstring tightness/shortness is very much prevalent among the undergraduate physiotherapy students. The reason might be the prolong study durations and lack of physical activities. The result showed statistically significant difference between hamstring muscle extensibility in both male and female Key words: Extension Angle, Flexion, Contracture, Fascitis